Prescription patterns of traditional Chinese medicine amongst Taiwanese children: a population-based cohort study - Hwey-Fang Liang; Yao-Hsu Yang; Pau-Chung Chen; Hsing-Chun Kuo; Chia-Hao Chang; Ying-Hsiang Wang; Kuang-Ming Wu (BMC, 2018)
Abstract Background Traditional Chinese medicine (TCM) has been used by Chinese patients and in many other countries worldwide. However, epidemiological reports and prescription patterns on children are few. Methods A cohort of 178,617 children aged 18 and under from one million randomly sampled cases of the National Health Insurance Research Database was analyzed for TCM prescription patterns. SAS 9.1 was applied and descriptive medicine utilization patterns were presented. Results The cohort included 112,889 children treated by TCM, with adolescents (12- to 18-year-olds) as the largest group. In the children's TCM outpatient visits, Chinese herbal remedies were the main treatment. The top three categories of diseases treated with Chinese herbal remedies were respiratory system; symptoms, signs, and ill-defined conditions; and digestive system. The top three categories using acupuncture were: injury and poisoning, diseases of the musculoskeletal system and connective tissue, and diseases of the respiratory system. Of the top ten herbal medicines prescribed by TCM physicians, the top nine herbal formulae and the top ten single herbs were associated with diseases of the respiratory system. Conclusion This study identified patterns of TCM prescriptions for children and common disease categories treated with TCM. The results provide a useful reference for health policy makers and for those who consider the usage of TCM for children.